Comparison of Hard Clustering and Soft Clustering Methods in Grouping Regencies/Cities in West Java Province Based on Regional Vulnerability Indicators to the Impact of Hydrometeorological Disasters in 2021 - Hanifah Vida Indrasari; Yuliagnis Transver Wijaya (Universitas Sebelas Maret, 2025)
Indonesia is an archipelagic country with a high incidence of hydrometeorological disasters and the number is increasing every year. One of the provinces in Indonesia with the highest number of hydrometeorological disasters is West Java Province, where 98.97 percent are hydrometeorological disasters. This is also supported by the characteristics of the area which is dominated by mountains, high rainfall, has 40 watersheds, and has six faults that are suspected to be still active so that it is vulnerable to hydrometeorological disasters. Research on regional vulnerability to hydrometeorological disasters can be carried out by grouping regions based on the same level of vulnerability using the clustering method. The purpose of this study was to group regencies or cities in West Java Province based on indicators of regional vulnerability to the impacts of hydrometeorological disasters in 2021. The clustering method used is hard clustering (single linkage, complete linkage, average linkage, ward's method and k-means) and soft clustering (Fuzzy C-Means). The most optimal method for grouping regencies or cities in West Java Province is the complete linkage method with a total of 4 clusters. The result is that all the resulting clusters are vulnerable to the characteristics of social vulnerability.Keywords: cluster analysis; hard clustering; natural disasters; regional vulnerability; soft clustering.